Atomic Ni Anchored Covalent Triazine Framework as High Efficient Electrocatalyst for Carbon Dioxide Conversion. (20th January 2019) - Lu, Chenbao; Yang, Jian; Wei, Shice; Bi, Shuai; Xia, Ying; Chen, Mingxi; Hou, Yang; Qiu, Ming; Yuan, Chris; Su, Yuezeng; Zhang, Fan; Liang, Haiwei; et al.
Abstract: Electrochemically driven carbon dioxide (CO2 ) conversion is an emerging research field due to the global warming and energy crisis. Carbon monoxide (CO) is one key product during electroreduction of CO2 ; however, this reduction process suffers from tardy kinetics due to low local concentration of CO2 on a catalyst's surface and low density of active sites. Herein, presented is a combination of experimental and theoretical validation of a Ni porphyrin‐based covalent triazine framework (NiPor‐CTF) with atomically dispersed NiN4 centers as an efficient electrocatalyst for CO2 reduction reaction (CO2 RR). The high density and atomically distributed NiN4 centers are confirmed by aberration‐corrected high‐angle annular dark field scanning transmission electron microscopy and extended X‐ray absorption fine structure. As a result, NiPor‐CTF exhibits high selectivity toward CO2 RR with a Faradaic efficiency of >90% over the range from −0.6 to −0.9 V for CO conversion and achieves a maximum Faradaic efficiency of 97% at −0.9 V with a high current density of 52.9 mA cm −2, as well as good long‐term stability. Further calculation by the density functional theory method reveals that the kinetic energy barriers decreasing for *CO2 transition to *COOH on NiN4 active sites boosts the performance. Abstract : Atomically dispersed NiN4 centers are rationally designed into a porous organic skeleton through an ionothermal approach. The as‐prepared porous materials are applied as electrocatalysts for carbon dioxide conversion and exhibit high carbon dioxide reduction selectivity toward CO production as well as long‐term stability.